The effects of distillers dried grains with solubles and corn gluten feed substitutes in growth diets of Boer-type goats - Tran, Sophia M.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
This study was commenced to obtain more knowledge in the growing field of goat production. The objective of the study is to compare goat growth and the economical values of the diets for Boer-type goats. The three types of protein sources that was studied for goat growth were corn gluten feed (CGF), distillers dried grains with solubles (DDGS), and soybean meal (SBM). Over a course of thirty-five days, five treatments were presented to a total of seventy-five Boer-type goats (26.9±0.2 kg, approximately 70 d of age). Goats were randomly allotted to pens with three goats/pen in a completely randomized design, with 5 replicants per treatment. Goats were fed isocaloric and isonitrogenous diets with different sources of protein. The five treatments with varying protein sources were: 1) SBM; 2) 100% DDGS/0% CGF; 3) 66% DDGS/33% CGF; 4) 33% DDGS/66% CGF; 5) 0% DDGS/100% CGF. Weights of feeders and goats were recorded to calculate ADG, ADFI, and G:F once every week for five weeks, with pen as the experimental unit. Data was analyzed with the GLIMMIX procedure of SAS (v. 9.4, Cary, NC), with the alpha value set at a 0.05. Dietary treatments did not affect (P>0.05) final BW, ADG, ADFI, or G:F. However, any use of a corn co-product as a substitute for SBM resulted in a $0.04/kg of feed savings, making SBM the least cost effective (P = 0.0008) of all the treatments. However, there was no observed impact of diet (P>0.05) on feed cost per kg of gain. As a result, the study suggests that DDGS and CGF can substitute SBM in growing Boer-type goat diets.
Keywords: Spring 2019